Costa Rica: Maritime Movement and Shipping Lines in the Port of Puntarenas 1833-1935 - Román Trigo, Ana Cecilia (Revista de historia., 2001)
By mid-19th Century, Costa Rica’s economy was firmly based on foreign trade and agricultural goods and most import and export trade was carried out through the port of Puntarenas. After 1882, when the Atlantic Railway began operations, port activity at Puntarenas declined. The number of vessels entering at Puntarenas between 1883 and 1935 and their respective tonnage is analyzed. The shipping lines serving the port and regularity of services they provided are also considered